Gender and the Building Up of Many ‘Peaces’: A Decolonial Perspective from Colombia dans Gender, conflict, peace, and UNSC resolution 1325 - Anctil Avoine, Priscyll; Tillman, Rachel; Mejía Jerez, Yuly Andrea (Gender, conflict, peace, and UNSC resolution 1325, 2018)
As we write this chapter about reinterpreting women’s roles in peacebuilding, Colombia is at a turning point. On November 24, 2016, the Revolutionary Armed Forces of Colombia—People’s Army (FARC-EP) and the national government signed a historical agreement that ended the 60-year-long armed conflict. How this peace and the social reconciliation that it requires will be implemented remain to be seen. At the peace negotiations roundtable, throughout the early years of the conversations, women were underrepresented, and even now gender inequality within public participation is far from being resolved. Although women have been acting equally with their male counterparts as rotating negotiators in these peace negotiations, the High Commissioner for Peace (Alto Comisionado para la Paz) affirms that only 25 percent of the plenipotentiary negotiators are women, and that while the Gender Subcommittee is an interesting accomplishment, it is still insufficient. Additionally, Colombia is facing the challenge of FARC-EP’s reintegration to civil society: between 33 percent and 40 percent of their troops are women and most of the DDR processes do not show a serious focus on gender in their programs.
Keywords: 2000 à aujourd'hui; 2010-2019; amérique latine; amériques; approches et analyses; colombie; corps; cours; discipline; féminisme décolonial; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; système colonial; systèmes d'oppressions; thématiques; violences